Intermediate Osteopetrosis with Hooked-Shaped Phalanges - Sangeeta Malik; Abhilash Panwar; Nagaraju Kamarthi; Sumit Goel (Journal of Indian Academy of Oral Medicine and Radiology)
Osteopetrosis is a bone condition caused by an abnormality in the function of osteoclasts. The absence of normal osteoclasts results in aberrant primary skeleton development and subsequent pathological bone turnover. When a blind patient presented to the hospital with recurrent pus discharge and was diagnosed with osteopetrosis, a unique radiological finding emerged.